Investigating the Effects of Long-Term Ambient Air Storage on the Sliding Properties of N-Alloyed MoSe2 Coatings - Talha Bin Yaqub; Irfan Nadeem; Muhammad Aneeq Haq; Muhammad Yasir; Albano Cavaleiro; Mitjan Kalin (Nanomaterials)
Transition metal dichalcogenide coatings have emerged as potential candidates for terrestrial and aerospace mobility applications. Among these, the alloyed MoSe2 coatings have displayed promising results while sliding in diverse environments. N-alloyed Mose2 coatings provide the additional benefit of overcoming the impact of PVD compositional variations on dry sliding, making them promising solid lubricants for mobility-sector applications. However, the impact of long-term storage has never been investigated for this rarely studied solid-lubricant system. This study investigates the tribological performance of direct current magnetron sputtered MoSeN coatings after 40 months of storage in an ambient atmosphere. Sliding tests were conducted under conditions consistent with pre-storage conditions. The results showed that coatings with 0 at. %, 22 at. %, 33 at. %, and 35 at. % N-alloying exhibited COF values nearly identical to the pre-storage results, with only a negligible increase in ~0.01. Similarly, all coatings displayed specific wear rates in the range of 10−7, aligning with earlier findings. The obtained results show that the sliding performance of MoSeN coatings does not deteriorate over time, highlighting their suitability for critical aerospace applications, where components and assembled parts may be stored for years before launching into space or in actual applications.